ANALISIS LAPORAN KEUANGAN DAN INDIKATOR KEBANGKRUTAN UNTUK MENILAI KINERJA KEUANGAN PADA INDUSTRI ROKOK DI BURSA EFEK INDONESIA - Fransiska Wahyu Lestari; Nela Sagita Dewi (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
One way that companies can do to keep the company survive, namely by analyzing thecompany's financial statements, which aims to determine the state and financial development of thecompany from year to year. The author conducted a study on tobacco industry companies listed on thestock exchanges of Indonesia.The method used by researchers in researching this research is by case study method withdata analysis technique using financial ratio method to know the cigarette company's financial positionin Indonesia stock exchange, and bankruptcy method of altman z-score model to know the company'ssustainability whether bankruptcy or no.From the results of analysis conducted by researchers, showed that of the four tobaccocompanies listed on the stock exchanges of Indonesia period 2013 to 2015 the financial position of PT.HM Sampoerna, Tbk which has good financial performance, and on bankruptcy indicator of PT. BentoelInternasional Investama, Tbk which is categorized as bankrupt. Thus, the company is expected toimprove itself by knowing the weaknesses that exist and can immediately make improvements in orderto obtain better results in the coming year.